Concentration of essential and toxic elements as a function of the depth of the soil and the presence of fulvic acids in a wetland in Cerrado, Brazil - Luko-Sulato, Karen [UNESP]; Rosa, Vinicius Atilio [UNESP]; Furlan, Lucas Moreira [UNESP]; Rosolen, Vania [UNESP] (Springer Nature, 2021)
The protection of wetlands is essential for sustainable development. The particular hydrology of wetlands creates conditions for the formation of hydric soils. Hydric soils are formed in oxide-reducing environments and perform important removal and re-oxidation of Fe and Mn oxides and hydroxides. They are also characterized by the formation of a superficial horizon enriched by the accumulation of organic matter. The objective of this study was to determine the concentration of essential (Co, Cu, Fe, Mn, Ni, Zn) and toxic (Al, Cd, Pb) elements in the soil solution in a wetland, surrounded by an intense agricultural activity area. The concentrations of the elements were evaluated according to the level of hydromorphy (border to the center) and the depth of the soil. The physical fractionation of these elements was also assessed (total and < 30 kDa), and the results were compared with the chemical speciation of these elements. Despite the high total concentrations of Al and Fe, the concentration of these elements was very low in the < 30 kDa fraction, which suggests that these elements are complexed with organic matter, in the form of hydroxides. Evidence of removal of Fe and Mn from the surface horizon was observed at the center of the wetland, where the highest level of hydromorphy is found. The results showed that the concentration of metals in the fraction < 30 kDa is insignificant, suggesting that the mechanisms of precipitation and/or adsorption to soil colloids play an important role in the regulation of this ecosystem.
Keywords: Chemical speciation; Hydric soil; Soil–water chemistry; Tropical wetland; Visual minteq